A Pragmatic Clinical Trial to Compare the Real-World Effectiveness of V-Go versus Standard Delivery of Insulin in Patients with Advanced Type 2 Diabetes - Mark J. Cziraky; Scott Abbott; Matt Nguyen; Kay Larholt; Elizabeth Apgar; Thomas Wasser; Poul Strange; Leon Shi; H. Courtenay Harrison; Beverly Everitt; Lynn Nowak (Journal of Health Economics and Outcomes Research)
**Background:** Many patients with type 2 diabetes mellitus (T2DM) do not have adequate glycemic control, leading to poor patient outcomes and high healthcare costs.